2022
DOI: 10.3390/en15072318
|View full text |Cite
|
Sign up to set email alerts
|

FEM Analysis: A Review of the Most Common Thermal Bridges and Their Mitigation

Abstract: The necessity to improve the energy saving potential of buildings is now a duty. European and national policies are being implemented to address the important decisions being made on this subject. For these reasons, several studies focus on this relevant topic. This paper review not only focusses on it but studies it in-depth. A commercial 3D simulation software was used to design a building sited in Palermo estimating the thermal losses before and after external envelope insulation. In particular, all the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The predicted mean vote (PMV) and predicted percentage of dissatisfied (PPD) were proposed by Fanger as comfort indicators [30]. Many studies related to PMV have been performed, including those on insulation performance [31][32][33][34].…”
Section: Analysis On 15 Januarymentioning
confidence: 99%
“…The predicted mean vote (PMV) and predicted percentage of dissatisfied (PPD) were proposed by Fanger as comfort indicators [30]. Many studies related to PMV have been performed, including those on insulation performance [31][32][33][34].…”
Section: Analysis On 15 Januarymentioning
confidence: 99%
“…Some studies analysed thermal bridges in buildings with lightweight concrete or clay bricks and RC structures and demonstrated that in these buildings, the most important thermal bridges were due to balconies, pillars, and the contact between the wall and window [5,8,9]. Curto et al provided a detailed analysis of thermal bridges in a building with tuff blocks and RC structures and drew up a list of "good practice" precautions to insulate the building and reduce the transmission heat losses in the thermal bridges to 9% of the total [10]. Thermal breakers emerge as an interesting, innovative solution to correct the thermal bridge between exterior walls and concrete slabs, both with and without a balcony, leading to a reduction in the space heating demand ranging from 5% to 25% according to the climate and the building geometry [8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the finite element analysis has the advantage of avoiding any geometric limitations and allows for an accurate calculation of the depicted construction detail according to the Standard EN ISO 10211:2017, with an error below ±5% [3]; furthermore, it provides both the heat flux and the temperature distribution in the building component, thus giving information on the possible occurrence of mould growth [10]. The use of 2D finite element numerical tools to determine the linear thermal transmittance has recently become very common, even in non-scientific applications such as for the release of Energy Performance Certificates.…”
Section: Introductionmentioning
confidence: 99%
“…These digital tools enable their users to fully harness the power of modeling and simulation in the design and analysis of a wide range of physical systems and processes. For example, finite-element modeling and simulation help in the design of safer bridges and buildings [3], while computational fluid dynamic simulations are vital in the aerodynamic and hydrodynamic analysis of fuel-efficient aircraft and ships [4], respectively.…”
Section: Introductionmentioning
confidence: 99%